A Mixed Approach for Approximation of Higher Order Linear Time Invariant Systems - Singh, Ramveer; Chatterjee, Kalyan; Singh, Jay (International Journal of Engineering and Technology, 2018)
This work suggests a technique for order reduction of larger order mathematical model into lower order by combining Modified Inverse Distance Measure (MIDM) and time moment matching criterion. The constant coefficients of the denominator of reduced model are attained by proposed algorithm named MIDM and numerator coefficients of the same are obtained by using the suitable number of time moments and Markov parameters in the set of equations of Improved Pade Approximations (IPA). The suggested method of order reduction is equally useful for both Single-Input Single-Output (SISO) and Multi-Input Multi-Output (MIMO) dynamic systems. The simplicity of the proposed method has been validated through various linear mathematical models taken from literature. To get into the touch of a researcher, the qualitative measure and dynamic analysis of the proposed reduced model output has been elaborated via error index and time/frequency response comparisons respectively.Â Â Â